The effect of annealing on the MR and exchange bias characteristics in dual spin valve with nano-oxide layer - Jang, SH; Kang, T; Kim, HJ; Kim, KY (ELSEVIER SCIENCE BV, 2002)
We investigated magneto resistance (MR) and exchange bias properties by annealing in the dual spin valve (SV) with nano-oxide layer (NOL). By analyzing effects of NOL in top and bottom pinned simple SVs, MR enhancement effect of NOL inserted in the bottom pinned layer was higher than that of NOL in the top pinned layer with annealing. By the enhanced specular scattering of electrons by NOL, the MR ratio of dual SV with NOL was increased to 15.5-15.9% with an annealing of 200-250degreesC. Exchange coupling constant J(ex) was improved rapidly as 0.13-0.16 erg/cm(2) by annealing in the bottom pinned layer, whereas the effect of annealing was not large in the top pinned layer with J(ex) of about 0.09-0.116 erg/cm(2). (C) Elsevier Science B.V. All rights reserved.
Keywords: MAGNETORESISTANCE; ENHANCEMENT